2019
DOI: 10.1101/808402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo CRISPR screening identifies RNF20/40 as epigenetic regulators of cardiomyocyte maturation

Abstract: Between birth and adulthood cardiomyocytes (CMs) undergo dramatic changes in size, ultrastructure, metabolism, and gene expression, in a process collectively referred to as CM maturation. The transcriptional network that coordinates CM maturation is poorly understood, creating a bottleneck for cardiac regenerative medicine. Forward genetic screens are a powerful, unbiased method to gain novel insights into transcriptional networks, yet this approach has rarely been used in vivo in mammals because of high resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Our results suggest that increased focus should be placed on trying to understand regulators of perinatal maturation in vivo, and determining discrepancies in activity of these regulators in vitro. In particular, we anticipate that entropy score can serve as a readout for mosaic-based screening systems for identifying perinatal CM maturation regulators [56]. Whether similar mechanisms underlie maturation arrest in other PSC-derived cells remains a question for further studies.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Our results suggest that increased focus should be placed on trying to understand regulators of perinatal maturation in vivo, and determining discrepancies in activity of these regulators in vitro. In particular, we anticipate that entropy score can serve as a readout for mosaic-based screening systems for identifying perinatal CM maturation regulators [56]. Whether similar mechanisms underlie maturation arrest in other PSC-derived cells remains a question for further studies.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Currently, the best systems to study in vivo pathways of maturation rely on mouse models of post-natal heart development amenable to genetic modification. Using an MYH7-YFP mouse line as a reporter of maturation in a CRISPR/Cas9 knockout screen, Vandusen et al found RNF20/40 to be key epigenetic regulators required for maturation [ 85 ]. Knockdown of estrogen-related receptor (ERR) isoforms ERRα and ERRβ postnatally showed that these regulators are critical for CM maturation [ 86 ].…”
Section: Gene Regulatory Network and Pathways Influencing CM Maturation And Transcriptomic Studiesmentioning
confidence: 99%
“…Mechanistically, pIC treatment regulates early Notch signaling and increases the epigenetic activating modification H3K9ac in cardiac myofilament genes promoter regions. In a recent study, in vivo CRISPR screening identifies RNF20/40 ( 123 ), which monoubiqui-tinates H2B at lysine 120 by exerting E3 ligase activity. RNF20/40 is essential for CMs maturation, which is proven to regulate metabolism during CM maturation directly.…”
Section: Posttranscriptional Regulationmentioning
confidence: 99%